Analysis of lower limb muscle activation patterns according to performance level in adolescent kayak athletes - Seo, Y.-H.; Park, S.-Y.; Joo, S.-H.; Kim, S.-K.; Han, K.-H. (Korean Journal of Sport Biomechanics, 2025)
Objective: This study aimed to investigate differences in lower limb muscle utilization strategies according to performance level among adolescent kayak athletes, and to provide foundational data for developing customized training programs. Method: The participants were nine adolescent athletes registered with the Korea Canoe Federation, categorized into a Medalist group (high performers) and a Non-medalist group (low performers) based on their national competition records within the past two years. Surface Electromyography (EMG) was used to collect muscle activation data for the Rectus Femoris (RF), Vastus Medialis Oblique (VMO), Vastus Lateralis (VL), Biceps Femoris (BF), Tibialis Anterior (TA), and Medial Gastrocnemius (MG) during stroke movements on a kayak ergometer. To compare muscle activation levels and muscle contraction onset timings between groups, the Mann-Whitney U test was employed. Results: The results revealed significant differences between groups in the activation of VL and BF muscles (p < .05). Additionally, a significant difference was found in the onset timing of the VMO (p < .05). Although no statistically significant differences were observed in the RF and MG muscles, opposite patterns of muscle utilization were found between the two groups. Conclusion: These findings suggest that the Medalist group was able to selectively recruit the necessary muscles in specific phases and optimize the timing of muscle contraction, thereby minimizing propulsion loss and energy consumption.